Prevailing practices of evaluation of teaching at Colombian universities - J. V Ortiz (Universidad del Magdalena, 2013)
This research describes the results on the assessment practices of teaching, research addressed within called: "Practices and Conceptions of Teaching Evaluation of Colombian Universities," developed as a doctoral thesis by the authoring seventeen universities that are part of the National Observatory Assessment Policies "ONPE" understanding the practices front eh perspective of Foucault, Michel in the sense of self that you make in this case the institution, subjects, outcome standards, imaginations, experiences, values, mandates and regulations that characterize different cultural activities, in the particular case, the evaluation of teaching and which are reflected in the way is specified and this practice is evident in the performance verification of teachers.